Aquaporin-4-antibody-positive Neuromyelitis Optica Spectrum Disorder in a Patient with Charcot-Marie-Tooth Disease Type 1A - Kobayashi, Shunsuke; Hatanaka, Yuki; Takahashi, Kazusa; Hamada, Yuichi; Kanbayashi, Takamichi; Sonoo, Masahiro (Internal Medicine, 2021)
Charcot-Marie-Tooth disease type 1A (CMT1A) is a hereditary peripheral neuropathy, and its involvement in the central nervous system (CNS) is very rare. We herein report a 51-year-old woman with CMT1A who suffered from recurrent optic neuritis and myelopathy. Under the diagnosis of anti-aquaporin-4 (anti-AQP4) antibody positive neuromyelitis optica spectrum disorder (NMOSD), we treated her successfully with corticosteroids. This is the first report of CMT1A complicated with anti-AQP4-positive NMOSD. Although the coexistence of the two disorders may simply be a coincidence, we speculated that immune cross-reaction between overexpressed peripheral myelin protein 22 and CNS myelin may have caused concomitant CMT1A and NMOSD.